Aortic adventitial fibroblast sensitivity to mitogen activated protein kinase inhibitors depends on substrate stiffness. (August 2017) - Scott, Rebecca A.; Kharkar, Prathamesh M.; Kiick, Kristi L.; Akins, Robert E.
Abstract: Adventitial fibroblasts (AFs) are key determinants of arterial function and critical mediators of arterial disease progression. The effects of altered stiffness, particularly those observed across individuals during normal vascular function, and the mechanisms by which AFs respond to altered stiffness, are not well understood. To study the effects of matrix stiffness on AF phenotype, cytokine production, and the regulatory pathways utilized to interpret basic cell-matrix interactions, human aortic AFs were grown in 5%, 7.5%, and 10% (w/v%) PEG-based hydrogels with Young's moduli of 1.2, 3.3, and 9.6 kPa, respectively. In 5% gels, AFs had higher proliferation rates, elevated monocyte chemoattractant protein-1 secretion, and enhanced monocyte recruitment. Significantly more AFs were α-smooth muscle actin positive in 7.5% gels, indicating myofibroblast development. AFs in 10% gels had low proliferation rates but produced high levels of interleukin-6 and vascular endothelial growth factor-A. Importantly, these modulus-dependent changes in AF phenotype were accompanied by alterations in the mitogen-activated protein kinase (MAPK) pathways contributing to the production of cytokines. These data indicate that complex cell regulatory changes occur with altered tissue stiffness and suggest that therapeutics affecting MAPK pathways may have altered effects on AFs depending on substrate stiffness.